2017
DOI: 10.1111/bph.13746
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic 1,3‐diketones attenuate lipopolysaccharide‐induced inflammatory response by an alternative magnesium‐mediated mechanism

Abstract: BACKGROUND AND PURPOSEToll-like receptor 4 (TLR4) plays a key role in the induction of inflammatory responses both in peripheral organs and the CNS. Curcumin exerts anti-inflammatory functions by interfering with LPS-induced dimerization of TLR4-myeloid differentiation protein-2 (MD-2) complex and suppressing pro-inflammatory mediator release. However, the inhibitory mechanism of curcumin remains to be defined. EXPERIMENTAL APPROACHBinding of bis-demethoxycurcumin (GG6) and its cyclized pyrazole analogue (GG9)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 59 publications
3
34
0
Order By: Relevance
“…In 1999, Jobin et al found that CUR has powerful anti-inflammatory effects because it suppressed the activation of NF-κB induced by various pro-inflammatory stimuli, through inhibition of IKKβ kinase activity or DNA binding of p65 [139,140]. Interesting studies analyzed more deeply this mechanism showing that curcumin contains α, β-unsaturated carbonyl group, and this group inhibits TLR-4 activation by interfering with receptor dimerization [140] an important step for the activation of downstream signaling pathways of this receptor [141,142]. According to Youn et al, the target of curcumin is TLR-4, but not the downstream components of TRIF pathway [141].…”
Section: Cur and Tlr-4 In Neuroinflammatory Diseasesmentioning
confidence: 99%
“…In 1999, Jobin et al found that CUR has powerful anti-inflammatory effects because it suppressed the activation of NF-κB induced by various pro-inflammatory stimuli, through inhibition of IKKβ kinase activity or DNA binding of p65 [139,140]. Interesting studies analyzed more deeply this mechanism showing that curcumin contains α, β-unsaturated carbonyl group, and this group inhibits TLR-4 activation by interfering with receptor dimerization [140] an important step for the activation of downstream signaling pathways of this receptor [141,142]. According to Youn et al, the target of curcumin is TLR-4, but not the downstream components of TRIF pathway [141].…”
Section: Cur and Tlr-4 In Neuroinflammatory Diseasesmentioning
confidence: 99%
“…Curcumin is a phenolic compound extracted from the rhizome of turmeric (Curcuma longa) that is usually used in Asia as an additive, spice and pigment [67][68][69][70][71][72]. Curcumin treatment suppressed the growth of colon cancer cells through retarding cell proliferation via inhibiting the Wnt/β-catenin pathway rather than by promoting apoptosis in mice [73].…”
Section: Colon Cancermentioning
confidence: 99%
“…This compound can modulate multiple signalling molecules such as transcription factors, enzymes, and secondary messengers, thereby controlling expression of a variety of genes, and is potentially effective in disease conditions associated with impaired regulation of such signalling pathways [ 7 ]. In particular, curcumin reduces LPS-induced activation and release of inflammatory cytokines by microglia and macrophages [ 8 13 ]. We and others demonstrated that curcumin and related compounds prevent activation of nuclear factor- κ B (NF- κ B), a transcriptional factor that regulates many genes involved in the initiation of inflammatory responses [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, curcumin reduces LPS-induced activation and release of inflammatory cytokines by microglia and macrophages [ 8 13 ]. We and others demonstrated that curcumin and related compounds prevent activation of nuclear factor- κ B (NF- κ B), a transcriptional factor that regulates many genes involved in the initiation of inflammatory responses [ 13 , 14 ]. This polyphenol also affects the immunophenotype of LPS-activated human THP-1 macrophages, especially the expression of M1 markers that are modulated through the NF- κ B pathway [ 10 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation